Review of “The Essential Whitall Perry” by Harry Oldmeadow - Bendeck Sotillos, Samuel (Journal of Contemporary Rituals and Traditions, 2024)
Whitall N. Perry (1920–2005) deserves wider recognition given the profundity of his insights, and the discernment he displays with respect to humanity’s great wisdom traditions. The editor of this volume has referred to him as “[t]he most authoritative traditionalist of American background” (Oldmeadow, 2000, p. 48). Readers may have encountered Perry’s work through A Treasury of Traditional Wisdom (1971)—a monumental compilation of spiritual texts from all the world’s religions. It is worth citing the following passage taken from the introduction to this landmark publication